Decolorization and degradation of Indigo Carmine dye from aqueous solution catalyzed by horseradish peroxidase. (January 2014) - Terres, Josias; Battisti, Rodrigo; Andreaus, Jürgen; de Jesus, Paulo Cesar
Abstract We have studied the kinetics of decolorization of aqueous solutions of the dye Indigo Carmine and its biocatalytic degradation by the enzyme horseradish peroxidase (HRP). Experiments were carried out with a dye concentration of 2.5 × 10−5 mol L−1 over a temperature range of 25–60°C and decolorization was monitored spectrophotometrically at 610 nm. Furthermore, the concentration of H2O2 (30%, 3%, 0.3%, 0.03% and 0.003%), essential for enzyme activation, the pH (4, 5, 6, 7, and 8) and the amount of enzyme (1, 2, and 3 mg) were varied. In the kinetic studies, it was observed that the decolorization curves followed first-order kinetics, which were used to determine the rate constants which ranged from 10−2 to 10−3 min−1, proving this to be a fast process, with color disappearance between 30 and 60 min. Acid conditions pH (4, 5, and 6), temperatures between 40°C and 60°C and hydrogen peroxide concentration between 0.3% and 0.003% with 2 mg of HRP enzyme, favored decolorization. The kinetic parameters [activation energy (Ea), activation enthalpy (ΔH#), activation Gibbs energy (ΔG#), and activation entropy (ΔS#)] were determined using the Arrhenius and Eyring equations. The results obtained for the best experimental conditions were as follows: Ea = 15.6 kJ mol−1, ΔH# = 18.2 kJ mol−1, ΔG# = 7.3 kJ mol− 1, and ΔS# = 0.036 kJ mol−1 K−1, with an efficiency of 99% of decolorization. Studies showed that HRP combined with H2O2 is effective in the decolorization and degradation of the Indigo Carmine dye.